Abdominal Wall Mycetoma Presented as Obstructed Incisional Hernia of Cesarean Section in Eastern Sudan - Osama A. Elhardello; Elsadig S. Adam; Ishag Adam (Hindawi Limited, 2007)
Mycetoma a worldwide disease frequently occurs in the tropics with the highest prevalence being in Africa. Madurella mycetomatis is the main causative organism of human eumycetoma in Sudan. The legs and feet were commonly the sites of the infection. A 22-year-old lady was presented with painful abdominal swelling around a previous caesarian section scar. A provisional diagnosis of obstructed incisional hernia was put. Histopathological examination revealed macroscopically four masses of soft tissue. Microscopic sections showed grains of Madurella mycetomatis.